2004
DOI: 10.3748/wjg.v11.i4.529
|View full text |Cite
|
Sign up to set email alerts
|

Expression of c-fos in gastric myenteric plexus and spinal cord of rats with cervical spondylosis

Abstract: c-fos expression in gastric myenteric plexus was dramatically associated with that in the spinal cord in rats with cervical spondylosis, suggesting that the gastrointestinal function may be affected by cervical spondylosis. If this hypothesis is confirmed by further studies, functional gastrointestinal diseases such as functional dyspepsia and irritable bowel syndrome could be explained by neurogastroenterology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…The FOS gene, whose full name is FOS proto-oncogene, is also named cfos. An immediate-early gene, the FOS gene has been shown to play a key role in cell growth, proliferation and differentiation [5][6][7] Kegg Enrichment Analysis A total of seventeen biological pathways were signi cantly enriched in the DEGs (Table S4), and further analysis revealed that the FOS gene was signi cantly enriched in the pertussis, leishmaniasis, Chagas disease (American trypanosomiasis), herpes simplex infection, and MAPK signaling pathways. Furthermore, the MAPK signaling pathway (Fig.…”
Section: De In the Skin Of Tan Sheep In The Birth And Er-mao Periodsmentioning
confidence: 99%
“…The FOS gene, whose full name is FOS proto-oncogene, is also named cfos. An immediate-early gene, the FOS gene has been shown to play a key role in cell growth, proliferation and differentiation [5][6][7] Kegg Enrichment Analysis A total of seventeen biological pathways were signi cantly enriched in the DEGs (Table S4), and further analysis revealed that the FOS gene was signi cantly enriched in the pertussis, leishmaniasis, Chagas disease (American trypanosomiasis), herpes simplex infection, and MAPK signaling pathways. Furthermore, the MAPK signaling pathway (Fig.…”
Section: De In the Skin Of Tan Sheep In The Birth And Er-mao Periodsmentioning
confidence: 99%
“…The method for gastric neuronal counterstaining was adapted from previous studies [6,18,19] . c-Fos cells were counted under microscopy in 25 ganglia from each antral preparation and expressed as a mean percentage count per myenteric ganglion.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…Immunohistochemical staining was car ried out using the avidin-biotin complex method as previously described [6,17] . The concentrations for rabbit anti-IL-1β, rabbit anti-caspase-3 and rabbit polyclonal anti-c-fos primary antibodies were 1:200, 1:200 (Sigma, Genetimes Technolog y Inc.) and 1:100 000 (diluted in NGS-T-PBS).…”
Section: Immunohistochemistrymentioning
confidence: 99%
See 2 more Smart Citations